A century of BCG: Impact on tuberculosis control and beyond. Issue 1 (6th May 2021) - Ahmed, Asma; Rakshit, Srabanti; Adiga, Vasista; Dias, Mary; Dwarkanath, Pratibha; D'Souza, George; Vyakarnam, Annapurna
Abstract: BCG turns 100 this year and while it might not be the perfect vaccine, it has certainly contributed significantly towards eradication and prevention of spread of tuberculosis (TB). The search for newer and better vaccines for TB is an ongoing endeavor and latest results from trials of candidate TB vaccines such as M72AS01 look promising. However, recent encouraging data from BCG revaccination trials in adults combined with studies on mucosal and intravenous routes of BCG vaccination in non‐human primate models have renewed interest in BCG for TB prevention. In addition, several well‐demonstrated non‐specific effects of BCG, for example, prevention of viral and respiratory infections, give BCG an added advantage. Also, BCG vaccination is currently being widely tested in human clinical trials to determine whether it protects against SARS‐CoV‐2 infection and/or death with detailed analyses and outcomes from several ongoing trials across the world awaited. Through this review, we attempt to bring together information on various aspects of the BCG‐induced immune response, its efficacy in TB control, comparison with other candidate TB vaccines and strategies to improve its efficiency including revaccination and alternate routes of administration. Finally, we discuss the future relevance of BCG use especially in light of its several heterologous benefits.